Biofilm formation onto starch fibres by Bacillus subtilis governs its successful adaptation to chickpea milk. Issue 4 (20th October 2020) - Rajasekharan, Satish Kumar; Paz‐Aviram, Tali; Galili, Shmuel; Berkovich, Zipi; Reifen, Ram; Shemesh, Moshe
Summary: Beneficial biofilms may confer effective adaptation to food matrices that assist bacteria in enduring hostile environmental conditions. The matrices, for instance, dietary fibres of various food products, might serve as a natural scaffold for bacterial cells to adhere and grow as biofilms. Here, we report on a unique interaction of Bacillus subtilis cells with the resistant starch fibresof chickpea milk (CPM), herein CPM fibres, along with the production of a reddish‐pink pigment. Genetic analysis identified the pigment as pulcherrimin, and also revealed the involvement of Spo0A/SinI pathway in modulating the observed phenotypes. Besides, through successful colonization of the CPM fibres, the wild‐type cells of B. subtilis displayed enhanced survivability and resilience to environmental stress, such as heat and in vitro gastrointestinal treatments. In total, we infer that the biofilm formation on CPM fibres is an adaptation response of B. subtilis for strategic survival. Abstract : Cells of probiotic bacterium Bacillus subtilis interact with the resistant starch fibers of chickpea through preferentially inducing biofilm formation pathway. The successfully colonized starch fibers enable enhanced survivability of the cells during different environmental stresses.